Relationship Length of Stay (Los) with Service Quality at the Emergency Room of Pratama Nawacita Datah Dave Hospital - Fransiska Song Gun; Andi Lis Arming Gandini; Rivan Firdaus (PT FORMOSA CENDEKIA GLOBAL, 2023)
Length of Stay (LOS) in the emergency room is used to see the level of density and clinical workload of nurses. This type of research is quantitative and the population is patients who receive health services in the Emergency Room of Pratama Nawacita Datah Dave Hospital with an average visit in 1 month is 37 people. The characteristics of the respondents were seen from the age of the majority of respondents> 60 years (51.4%), female sex totaling 19 people (51.4%), the diagnosis of disease most of the respondents with hypertension amounted to 17 people (45.9%). The level of Length of Stay (LOS) is mostly from less respondents (59.5%) and service quality is mostly from less respondents (56.8%) There is a relationship between Length of Stay (LOS) and service quality (p value 0.042 < α : 0.05). That means there is a relationship between Length of Stay (LOS) and service quality.